A Compact asymmetric monopole antenna with electrically coupled SRR for WiMAX/WLAN/UWB applications. Issue 9 (September 2015) - Rajeshkumar, V.; Raghavan, S.
ABSTRACT In this article, a very compact printed asymmetric rectangular monopole antenna with an electrically coupled split ring resonator (SRR) is presented. The operating frequencies cover the worldwide interoperability for microwave access (WiMAX), wireless local area network (WLAN), and ultra wideband (UWB) applications. The asymmetric monopole is fed by a microstrip line, whereas the SRR is inductively coupled with the radiating element. The electric field‐coupled SRR yields its resonance at 3.5 GHz in addition to the fundamental wideband resonance obtained by the asymmetric monopole. The measured operating bands (3.48–3.62 GHz), (5.1–11.12 GHz) are suitable for WiMAX and 5 GHz WLAN bands. Consequently, the overall operating bands of the antenna cover the UWB range with the exception of 3.1–3.48 and 3.62–5.1 GHz range. The proposed antenna has a very compact size of 13 × 15 × 1.6 mm3. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2194–2197, 2015